2021
DOI: 10.1021/acs.chemrestox.1c00262
|View full text |Cite
|
Sign up to set email alerts
|

A Catecholaldehyde Metabolite of Norepinephrine Induces Myofibroblast Activation and Toxicity via the Receptor for Advanced Glycation Endproducts: Mitigating Role of l-Carnosine

Abstract: Monoamine oxidase (MAO) is rapidly gaining appreciation for its pathophysiologic role in cardiac injury and failure. Oxidative deamination of norepinephrine by MAO generates H 2 O 2 and the catecholaldehyde 3,4-dihydroxyphenylglycolaldehyde (DOPEGAL), the latter of which is a highly potent and reactive electrophile that has been linked to cardiotoxicity. However, many questions remain as to whether catecholaldehydes regulate basic physiological processes in the myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Furthermore, AGE can alter SOD expression and impact the expression of proteins related to ECM remodeling [ 21 ]. Thus, the increase in ROS, the accumulation of catechol-modified proteins, the expression and secretion of type I and type III collagen and pro-fibrotic activation markers (such as STAT3) explain the occurrence of extracellular matrix remodeling [ 36 ]. Increased AGE has also been implicated in fibroblast activation and proliferation in DM [ 37 ].…”
Section: Molecular Mechanisms Involved In Diabetes-induced Cardiac Remodelingmentioning
confidence: 99%
“…Furthermore, AGE can alter SOD expression and impact the expression of proteins related to ECM remodeling [ 21 ]. Thus, the increase in ROS, the accumulation of catechol-modified proteins, the expression and secretion of type I and type III collagen and pro-fibrotic activation markers (such as STAT3) explain the occurrence of extracellular matrix remodeling [ 36 ]. Increased AGE has also been implicated in fibroblast activation and proliferation in DM [ 37 ].…”
Section: Molecular Mechanisms Involved In Diabetes-induced Cardiac Remodelingmentioning
confidence: 99%
“…The aldehyde mixture included 4-HNE (lipid-derived aldehyde), 3,4-dihydroxyphenylacetaldehyde (DOPAL) and 3,4-dihydroxyphenylglycolaldehyde (DOPEGAL). The latter are dopamine and norepinephrine metabolites, respectively, which we have previously shown are biogenic aldehydes formed in heart and are increased in myocardial tissues from patients with T2 diabetes ( Monroe and Anderson, 2021 ; Nelson et al, 2021 ). We found that collagen cross-linking was stimulated by these aldehydes in the absence ( p = 0.0545) and presence of glucose, as indicated by higher shear modulus of the suspension ( Figure 3D ).…”
Section: Resultsmentioning
confidence: 78%
“…In addition, CaMKII can also be activated by oxidative stress and contribute to arrhythmias 60 . Previous work from our group and others have shown that cardiac MAO-A are robust generators of H2O2 and reactive catecholaldehydes 12,61 , the latter of which causes disruptions in mitochondrial oxidative phosphorylation (OxPHOS) 62 , and stimulates proinflammatory/pro-fibrotic signaling in the myocardium 63 . A decrease in oxidative stress in cMAO-A def hearts following catecholaminergic overload would thus predictably avoid the overaction of CaMKII and other adverse effects, all of which could contribute to the reduced arrhythmogenesis found in the cMAO-A def mice.…”
Section: Discussionmentioning
confidence: 97%